TANGGAPAN PEMBACA TERHADAP NOVEL AYAT-AYAT CINTA KARYA HABIBURRAHMAN EL SHIRAZY: TINJAUAN RESEPSI SASTRA - Rusdian Noor Dermawan; Cahya Ajisaputra (CARAKA, 2014)
The objectives of the research are (1) to describe the respond of readers towards love verse novel (novel Ayat-Ayat Cinta), (2) to describe horizon expectation of readers towards love verse novel, and (3) to describe the factors influencing the different responds and horizon expectation of readers. The data of the research is paragraph unity covering the respond of readers towards love verse novel and the source of the data are articles and paper published in mass media and electronic media including internet. The instrument is the researcher supplied by a set of concept about readers, respond to readers, and horizon expectation. The data were collected by observation and data analysis technique is done by descriptive analysis technique. The results are (1) most of the readers (80-100%) give positive substance as the theme, plot, characters and characterization, setting, the point of view, language style, title, the technique of storytelling, spelling, solution, language and extrinsic novel of love verse. (2) before reading the novel most of reader expect that they expect that it will be appropriate with the twelve elements in the novel, so they can easily understand the novel with full commendation, (3) the factors that make the differences are caused by the different stressing to the material, the lack of knowledge about their literary understanding, their experience of life about literary works.